The application of the Analytic Hierarchy Process method to the selection of dominant factors for adolescents who are prone to insecurity - Indra Riyana Rahadjeng; Muhammad Noor Hasan Siregar (IJISTECH (International Journal of Information System and Technology), 2021)
Teens are often stressed, worried, and overly insecure as a result of their high expectations. The feelings that occur during adolescent development can create and increase feelings of insecurity in their lives, which has a negative impact. Adolescents with an excessive sense of insecurity can suffer from mental disruption, which can lead to serious mortality. Of course, these factors can have a negative impact on adolescents' mental health. Adolescents' minds and psyches can be disrupted by mental illness. The goal of this study is to identify the dominant factor among a number of factors that can lead to insecurity when using the Decision Support System (DSS) technique. Analytical Hierarchy Process is the DSS method used (AHP). The data used in this study was gathered through observations and interviews with adolescents using a random questionnaire. Six factors were derived from observations and interviews: social environmental factors (A1), family environmental factors (A2), social media factors (A3), insecure factors (A4), trauma factors (A5), and education and work factors (A6). The results of the AHP method show that the main factors for adolescents who are easily insecure are social environmental factors (first), social media factors (second), and family environmental factors (third) (third).